INCREASING ADOLESCENT KNOWLEDGE THROUGH PROVIDING EDUCATION ABOUT FREE SEX - Octaviani Laput, Dionesia; Damaiyanti Putri Raden, Natalia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Adolescence is the transition from childhood to adulthood, beginning between the ages of 8 and 14. Information from the National Population and Family Planning Agency (BKKBN) from a survey by the Indonesian Health Office in 2018 and from the results of a population survey about the number of free sex cases that continue to increase every year, also reached 5.6% of Indonesian adolescents have had premarital sex. This service activity aims to increase adolescent knowledge about free sex by using lectures, question and answer, and evaluation methods to obtain results that there is an increase in adolescent knowledge about free sex after being given counseling which can be seen from the results of the pretest and posttest so that it can be concluded that the importance of early cultivation of knowledge about free sex in adolescents is very good for supporting a healthy adolescent future. Adolescents must be reminded of moral values so that later adolescents understand free sex and understand the risks borne by doing so so that adolescents can develop without free sex.